MO977POTENTIAL INTERACTIONS BETWEEN UREMIC TOXINS AND DRUGS: AN APPLICATION IN KIDNEY TRANSPLANT RECIPIENTS TREATED WITH CALCINEURIN INHIBITORS*. (29th May 2021) - André, Camille; Choukroun, Gabriel; Benis, Youssef; Kamel, Saïd; Bodeau, Sandra; Liabeuf, Sophie
Abstract: Background and Aims: In addition to affecting glomerular filtration rate, chronic kidney disease (CKD) changes the absorption, distribution and nonrenal clearance of a number of drugs. The uremic toxins that accumulate with as renal function deteriorates can potentially affect drug pharmacokinetics. Given the requirement for therapeutic drug monitoring (TDM) with most immunosuppressants, the latter are good models for understanding the potential impact of uremic toxins on blood concentrations of drugs. We focused on two calcineurin inhibitors (tacrolimus and cyclosporine) with similar pharmacological properties: low but variable oral bioavailability, strong binding to plasma proteins (albumin for tacrolimus and lipoproteins for cyclosporine), metabolism by cytochrome P450 3A4/5, and excretion in the bile. Our starting hypothesis was that uremic toxins influence the exposure of immunosuppressants. The study's objective was to determine whether plasma concentrations of certain uremic toxins were correlated with blood concentrations of the two immunosuppressants. Method: DRUGTOX was a cross-sectional study of 403 adult patients followed up after kidney transplantation at Amiens University Medical Center (Amiens, France) and who had undergone TDM of calcineurin inhibitors between August 4th, 2019, and March 11th, 2020. The patients had been treated daily with oral tacrolimus or cyclosporine. Two groups were constituted: 203 patients with low uremic toxin levels (estimated glomerular filtration rate (eGFR) according to the Modification of Diet in Renal Disease equation >40 mL/min/1.73m2) and 200 patients with high uremic toxin levels (eGFR <40 mL/min/1.73m2). For each patient, immunosuppressant trough concentrations (C0) were measured in whole-blood samples and then normalized against the total daily dose: C0/D ratio. After centrifugation, the sample was assayed for five uremic toxins (urea, trimethylamine N-oxide (TMAO), indole acetic acid (IAA), para-cresylsulfate (PCS), and indoxylsulfate (IxS)) using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Univariate and multivariate logistic regressions were used to evaluate the associations between plasma uremic toxin levels and the blood tacrolimus or cyclosporine C0/D ratio. Results: The median [interquartile range] age was 56 [48-66] and the median eGFR was 41 [30-57] ml/min/1.73 m2. The majority of the patients (56.5%) were at CKD stage 3. A total of 248 (61.5%) patients were being treated with tacrolimus and 155 (38.5%) were being treated with cyclosporine. The median time between transplantation and study inclusion was 6.5 years. Plasma urea, TMAO, IAA, PCS and IxS levels rose progressively with the CKD stage. In a univariate logistic analysis, age, sex, BMI, urea, IxS and PCS were significantly associated with an increment in the tacrolimus C0/D ratio. A multivariate analysis revealed an independent association with IxS (odds ratio [95% confidence interval]: 1.36 [1.00; 1.85], after adjustment for sex, age and BMI, whereas adjustment for age weakened the association for PCS (OR: 1.22 (0.99; 1.55)) and urea (OR: 1.71 (0.93; 3.16)). In a univariate logistic analysis, age, sex, BMI, and the TMAO level (but neither PCS, IxS, IAA nor urea) were significantly associated with an increment in the cyclosporine C0/D ratio. Conclusion: Even though TDM and dose adaptation of immunosuppressants keeps levels within the therapeutic window, elevated exposure to tacrolimus (but not cyclosporine) is associated with an accumulation of PCS, IxS and urea. This might be explained by an interaction between tacrolimus and highly albumin-bound uremic toxins. Our findings may have implications for other drugs that bind with high affinity to albumin (since an elevated free fraction might lead to unexpected exposures, which can alter their efficacy and/or tolerance).